2020
DOI: 10.1038/s41597-020-00666-0
|View full text |Cite|
|
Sign up to set email alerts
|

Genome assembly and annotation of Meloidogyne enterolobii, an emerging parthenogenetic root-knot nematode

Abstract: Root-knot nematodes (genus Meloidogyne) are plant parasites causing huge economic loss in the agricultural industry and affecting severely numerous developing countries. Control methods against these plant pests are sparse, the preferred one being the deployment of plant cultivars bearing resistance genes against Meloidogyne species. However, M. enterolobii is not controlled by the resistance genes deployed in the crop plants cultivated in Europe. The recent identification of this species in Europe is thus a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 68 publications
6
51
0
Order By: Relevance
“…The only support values lower than 0.9 concerned the relative branching order of the RKN within clade I, sensu De Ley ( M. arenaria , M. enterolobii , M. floridensis , M. incognita and M. javanica ). This observation is not particularly surprising, as these RKN species underwent complex hybridization and polyploidization events, with a probable same common or very similar maternal origin and distinct paternal progenitors [ 23 , 24 , 29 , 78 ]. As a result, some genome regions are highly similar between these species, while copies of the region are highly divergent within a same species.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The only support values lower than 0.9 concerned the relative branching order of the RKN within clade I, sensu De Ley ( M. arenaria , M. enterolobii , M. floridensis , M. incognita and M. javanica ). This observation is not particularly surprising, as these RKN species underwent complex hybridization and polyploidization events, with a probable same common or very similar maternal origin and distinct paternal progenitors [ 23 , 24 , 29 , 78 ]. As a result, some genome regions are highly similar between these species, while copies of the region are highly divergent within a same species.…”
Section: Discussionmentioning
confidence: 97%
“…Describing more thoroughly the effector protein repertoire and dissecting their functions is therefore important for the development of novel nematode control strategies. Over the years, the availability of several RKN genomes provided new resources for the identification of complete sets of candidate effectors in these species [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Although nematode effectors are very diverse, many share common features with other secreted animal proteins, such as the presence of N-terminal signal peptides for secretion, or the absence of transmembrane domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, the availability of several RKN genomes provided new resources for the identification of complete sets of candidate effectors in these species [20][21][22][23][24][25][26][27][28][29]. Although nematode effectors are very diverse, many share some common features with other secreted animal proteins, such as the presence of N-terminal signal peptides for secretion, or the absence of transmembrane domains.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the M. incognita genome employed in this original study [20] was later shown to be partially incomplete, with an improved version published afterwards [23]. Meanwhile, the availability of genome sequences for additional RKN species [24,[26][27][28][29], as well as for other plant-parasitic nematode species, including cyst nematodes [15,34,35], stem and bulb nematodes [36,37], or the more distantly related pine wilt disease nematode [38], greatly expanded the diversity of genomes for plant-parasitic nematode species. Similar genome sequencing efforts were also accomplished in the other nematode clades, including in animal parasites and free-living species, offering a novel opportunity for nematode comparative genomics.…”
Section: Introductionmentioning
confidence: 99%